Radiation-induced bystander effect and its clinical implications - Tang, Haoyi; Cai, Luwei; He, Xiangyang; Niu, Zihe; Huang, Haitong; Hu, Wentao; Bian, Huahui; Huang, Hao (Frontiers in Oncology, 2023)
For many years, targeted DNA damage caused by radiation has been considered the main cause of various biological effects. Based on this paradigm, any small amount of radiation is harmful to the organism. Epidemiological studies of Japanese atomic bomb survivors have proposed the linear-non-threshold model as the dominant standard in the field of radiation protection. However, there is increasing evidence that the linear-non-threshold model is not fully applicable to the biological effects caused by low dose radiation, and theories related to low dose radiation require further investigation. In addition to the cell damage caused by direct exposure, non-targeted effects, which are sometimes referred to as bystander effects, abscopal effects, genetic instability, etc., are another kind of significant effect related to low dose radiation. An understanding of this phenomenon is crucial for both basic biomedical research and clinical application. This article reviews recent studies on the bystander effect and summarizes the key findings in the field. Additionally, it offers a cross-sectional comparison of bystander effects caused by various radiation sources in different cell types, as well as an in-depth analysis of studies on the potential biological mechanisms of bystander effects. This review aims to present valuable information and provide new insights on the bystander effect to enlighten both radiobiologists and clinical radiologists searching for new ways to improve clinical treatments.